Minimally invasive treatment of intracerebral hemorrhage. (August 2015) - Rennert, Robert C; Signorelli, Jason W; Abraham, Peter; Pannell, Jeffrey S; Khalessi, Alexander A
<x xml:space="preserve">Abstract</x> Intracerebral hemorrhages (ICH) cause high levels of morbidity and mortality. Secondary neuronal injury from perihematomal edema is thought to contribute to poor outcomes. Surgical evacuation of ICH is a theoretically promising approach, yet clinical data on the efficacy of standard craniotomy approaches is limited. Recent exploration of minimally invasive techniques for ICH removal includes stereotactic surgery combined with intra-clot thrombolysis, as well as endoscopic hematoma evacuation. Ongoing trials have demonstrated the safety of such minimally invasive approaches, and pending efficacy data from these studies is likely to change the standard management of ICH.